The social world of children learning to talk - Risley, Todd R.; Hart, Betty (Paul H. Brookes, 2007)
The social dance of american family life. Observing children and families talking. A social world. developmental change. becoming partners. Staying and playing. practicing. The range among well-functioning families. Meaningful differences.Talking as a social dance
Keywords: Language Acquisition